Day 7 of Kanjuruhan Tragedy: Twitter Data Analysis - Moch Fuad Nasvian; Moch. Aan Sugiharto; Muhammad Fadhlillah Setiamukti (Universitas Muhammdiyah Yogyakarta, 2023)
The Kanjuruhan Stadium tragedy on 1 October 2022 became the second deadliest in the history of football. Leaders of many countries sent condolence letters to Joko Widodo, the President of Indonesia. The National Commission on Human Rights commissioner stated that the Kanjuruhan tragedy was a human rights case. The tragedy led to the rise of social movement and digital activism (DMO) through the hashtags #KanjuruhanDisaster #UsutTuntas #PrayforKanjuruhan and #Aremania. This study explains the social network formed by the aforementioned hashtags, the actors involved, and sentiment analysis. The data set crawled using Netlytic.org found 9,944 DMO tweets using the hashtags out of 10,000 tweets. The results of this study prove that DMO on the Kanjuruhan tragedy through the hashtag #KanjuruhanDisaster #UsutTuntas #PrayforKanjuruhan #Aremania has a high number of neutral sentiments indicating that the netizen is still in the phase of mourning and using neutral language to sarcast the authority. The network property data show that there is no feedback and explanation form the authority to reduce the tension of netizens. Low centralization rate between actors shows that digital activism occurs organically and is not controlled by a particular actor or organization.